Cenozoic uplift and subsidence in the North Atlantic region: Geological evidence revisited - Anell, I.; Thybo, H.; Artemieva, I.M. (Tectonophysics, 2009)
The topographic evolution of the “passive” margins of the North Atlantic during the last 65 Myr is the subject of extensive debate due to inherent limitations of the geological, geomorphological and geophysical methods used for studies of uplift and subsidence. We have compiled a database of sign, time and amplitude (where possible) of topographic changes in the North Atlantic region during the Cenozoic (65–0 Ma). Our compilation is based on published results from reflection seismic studies, AFT (apatite fission track) studies, VR (vitrinite reflectance) trends, maximum burial, sediment supply studies, mass balance calculations and extrapolation of seismic profiles to onshore geomorphological features. The integration of about 200 published results reveal a clear pattern of topographic changes in the North Atlantic region during the Cenozoic: (1) The first major phase of Cenozoic regional uplift occurred in the late Palaeocene–early Eocene (ca 60–50 Ma), probably related to the break-up of the North Atlantic between Europe and Greenland, as indicated by the northward propagation of uplift. It was preceded by middle Palaeocene uplift and over-deepening of some basins of the North Sea and the surrounding areas. (2) A regional increase in subsidence in the offshore marginal areas of Norway, the northern North Sea, the northern British Isles and west Greenland took place in the Eocene (ca 57–35 Ma). (3) The Oligocene and Miocene (35–5 Ma) were characterized by regional tectonic quiescence, with only localised uplift, probably related to changes in plate dynamics. (4) The second major phase of regional uplift that affected all marginal areas of the North Atlantic occurred in the Plio-Pleistocene (5–0 Ma). Its amplitude was enhanced by erosion-driven glacio-isostatic compensation. Despite inconclusive evidence, this phase is likely to be ongoing at present.